Latin American electricity markets and renewable energy sources: The Argentinean and Chilean cases - Guzowski, Carina (2010)
From the mid eighties on, most of Latin American Countries reformed their energy systems. The impact of these reforms over electricity markets was different in each case. However, in the majority of these cases there was a shift to private participation, instead of State, and a convergence of electricity systems to hydro and thermal technologies. This is the case of Argentina and Chile. In this context, the aim of this paper is to discuss the current situation of renewable energies in Chilean and Argentinean electric markets and the potential to increase their share in total energy supply. To this purpose, we firstly study electricity deregulation process and its current situation. Secondly, we analyze renewable energy share in these electricity systems comparatively to worldwide situation. Finally, we briefly present the policy instruments used in each country. © 2009 Professor T. Nejat Veziroglu. Published by Elsevier Ltd. All rights reserved.